2008
DOI: 10.1111/j.1468-2494.2008.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined retinol–lactose–glycolic acid effects on photoaged skin: a double‐blind placebo‐controlled study

Abstract: The objective of this study was to assess the efficacy of the combination of retinol, lactose and glycolic acid applied topically on photodamaged skin. Forty female volunteers were enrolled in a double-blind, randomized placebo-controlled clinical study. A cream containing retinol, lactose and glycolic acid was applied on one side of the face and a placebo cream on the other side, twice daily for 12 weeks. Skin photoageing signs were assessed clinically, whereas skin microrelief and moisturization were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
(29 reference statements)
3
3
0
Order By: Relevance
“…We observed decreases in Ra and Rz of approximately 8% at 4 weeks and 11‐12% at 8 weeks. This compares favorably with other studies using similar methods and known anti‐aging ingredients 35,36,38–41 …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We observed decreases in Ra and Rz of approximately 8% at 4 weeks and 11‐12% at 8 weeks. This compares favorably with other studies using similar methods and known anti‐aging ingredients 35,36,38–41 …”
Section: Discussionsupporting
confidence: 82%
“…Many cosmetic ingredients and products have been shown in vivo to provide anti‐aging skin benefits, e.g., combined retinol–lactose–glycolic acid treatment, 35 a sphingolipid derivative, 12 a palmitoyl pentapeptide, 36 topical ascorbic acid, 37 adenosine, 38 a niacinamide containing anti‐aging formulation, 39 a complex of anti‐aging ingredients comprising a mix of peptides, vitamins and niacinamide, 40 a variety of natural extracts and peptides, 11,41,42 lipoic and hydroxyacids acid 43–45 . Of these, hydroxyacids can potentially have negative somatosensory effects on skin that can limit consumer compliance and therefore efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Here we have shown that the TPC achieved comparable benefits to retinol, without the irritation or formulation restrictions associated with this cosmetic ingredient. Furthermore, skin relief measurements obtained in our studies were comparable to a combined retinol–lactose–glycolic acid treatment, 29 a sphingolipid derivative, 30 a palmitoyl pentapeptide, 31 topical ascorbic acid, 32 adenosine, 33 a niacinamide containing anti‐aging formulation, 34 and a recently published formulation containing complex of anti‐aging ingredients comprising a variety of natural extracts and peptides 19 . These results add to the growing data on the efficacy of topical peptides 35 …”
Section: Discussionsupporting
confidence: 56%
“…There is increasing evidence documenting the effects of ‘antiaging’ cosmetic moisturizers on the signs of photodamaged skin. Typical agents used in these moisturizers include hydroxyacids, retinol, and its esters, salicyloylphytosphingosine, peptides, adenosine, niacinamide, creatine and folic acid, peroxisomal proliferator activated receptor agonists, hyaluronic acid fragments, and a variety of antioxidants including ascorbic acid and lipoic acid . Many of these agents have complex effects on the skin ranging from increasing dermoepidermal membrane restructuring through to inhibition of matrix metalloprotease activity and improving epidermal differentiation all of which are perturbed in photodamaged skin.…”
Section: Introductionmentioning
confidence: 99%